Morphological and Functional Adaptations in the Heart of Young Athletes Due to Endurance Training - Rafailakis Λευτέρης; Soulas Δημήτριος; Jamurtas Αθανάσιος Ζ. (Inquiries in Physical Education and Sport, 2015)
The main goal of the present review is to investigate the effect of endurance training on the morphology and function of the heart. Research on that topic is scarce and almost absent on endurance training exclusively. Research based on adult athletes as well as young athletes was reviewed and was found that the cardiac adaptations between adults and adolescents are similar. Even though the existence of the “athlete’s” heart is a common belief among the researchers, the Morganroth’s hypothesis which prevailed for many years, seems to be partially verified, since the concentric cardiac adaptation of athletes of dynamic sports does not seem to apply to the same degree as the increase of left ventricular wall thickness among the endurance sports athletes, as more recent research shows. It seems that in all athletes’ categories there is an increase in end-diastolic left ventricular volume that occurs concurrently with the increase on wall thickness. However, the cardiac hypertrophy is more apparent on ultra-distance athletes who show extremely high rates of this adaptation. Although the adaptations in the right ventricle and atrium have not been sufficiently investigated, it seems that there is a prevailing uniform development of the heart as a result of exercise. The body surface area affects positively the cardiac hypertrophy, while, as a result of the above, men show higher rates in all relevant parameters. Ejection fraction seems not to be affected due to training whereas all relevant to systolic and diastolic function are modified. The hormonal profile of children younger than the twelve years of age does not help in the development of the heart and is required at least two years of training in order to observe significant changes. In young athletes, the increase in left ventricular end-diastolic volume precedes the increase in wall thickness of the left ventricle, something that happens in opposite fashion in adults. Many questions regarding the morphological and functional changes of the heart due to intense training are still remaining.